Marketing Strategy Of Tomatoes (Solanum Lycopersicum Mill) Using Soar And Qspm Methods In The Argoayuningtani Farmers Group, Senden Village, Selo District Boyolali District - Latif Mahmudi, Wildana; Prasetyo, Agung; suswadi; Ridyo Arum, Mutiarra; Prasetyowati, Kusriani (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2024)
This research aims to: (1) determine the internal factors that are the strengths and aspirations of tomatoes marketing in Senden Village, Selo District, Boyolali Regency. (2) knowing the external factors that become opportunities and results in tomato marketing in Senden Village, Selo District, Boyolali Regency. (3) knowing the marketing strategy for tomatoes in Senden Village, Selo District, Boyolali Regency. The method used in this research is quantitative descriptive. The selection of research locations was carried out purposively, namely Senden Village, Selo District, Boyolali Regency. Sampling with key informants. The types of data used are primary data and secondary data. Data collection techniques using observation, interviews and recording. The data analysis used is the SI and AI matrix, IE matrix and SOAR (Strength, Opportunity, Aspiration, Result) analysis. The results of the analysis from this research are that the SI matrix has a score of 2.28 and the AI matrix has a score of 2.31. The IE matrix analysis is in cell I, meaning this strategy is to grow and build (Hold and Maintain) with an intensive strategy consisting of market penetration, development and product development that focuses on existing tomatoes. The results of the SOAR analysis show five alternative strategies.